2011
DOI: 10.1088/1674-1056/20/3/034202
|View full text |Cite
|
Sign up to set email alerts
|

Approximate analytical expressions of apertured broadband beams in the far field

Abstract: Approximate analytical expressions of apertured broadband beams in the far field * Lu Shi-Zhuan(陆世专) a)b) † , You Kai-Ming(游开明) b) , Chen Lie-Zun(陈列尊) b) , and Wang You-Wen(王友文) b)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In recent years, there have been a few theoretical articles dealing with the self-focusing performance of the gradient-index material, [11,12] the propagation property of the Gaussian beam, [13,14] the imaging quality enhancement of the optical coherence tomography, [15] etc. In addition, Jung et al [16] reported a numerical analysis of the gradient-index lens based optical probe.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there have been a few theoretical articles dealing with the self-focusing performance of the gradient-index material, [11,12] the propagation property of the Gaussian beam, [13,14] the imaging quality enhancement of the optical coherence tomography, [15] etc. In addition, Jung et al [16] reported a numerical analysis of the gradient-index lens based optical probe.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the mathematical difficulty in dealing with the propagation of ultrashort pulsed beams with constant waist width, usually numerical results or approximate propagation expressions are found in the past studies. Beyond these, there are few studies focused on the diffraction of pulsed beam from the hard edges [9][10][11].…”
Section: Introductionmentioning
confidence: 99%